Pengaruh Penambahan Nd2O3 dan Fe2O3 Pada Sistem Elektrolit Padat Gadolinia Doped Ceria (GDC) Untuk Aplikasi Sel Bahan Bakar Oksida Padat Suhu Menengah [Effect of Nd2O3 and Fe2O3 Addition on Gadolinia Doped Ceria (GDC) Solid Electrolyte System For IT-SOFC] - Akbar, Muhammad Faisal; Dilasari, Bonita; Soepriyanto, Syoni; Suhendar, Dadan (Jurnal Metalurgi, 2022)
Gadolinia Doped Ceria (GDC) is a solid electrolyte contender for intermediate-temperature SOFCs. However, more development of this solid electrolyte is required to improve its ionic conductivity. As a result, we will investigate the effect of Nd2O3 and Fe2O3 addition on GDC solid electrolytes to boost ionic conductivity. Solid electrolytes of the composition Ce0.9Gd0.2MxO1.9 (M = Nd, Fe) (x = 0%, 2,5% , 5%, and 7.5%) were synthesized using mixed oxide method and formed into pellets with a diameter of 1 cm. The pellets were sintered at 1200oC and 1400oC for 4 hours in an argon environment then the EIS test was performed at 450-650oC. The results showed that the Nd2O3 and Fe2O3 added were totally dissolved in the ceria structure and produced single-phase cubic fluorite CeO2. GDC solid electrolyte with Fe2O3 addition produces higher densification than Nd2O3 addition, where the value reaches 75% in the sample sintered at 1400oC. However, the addition of Nd2O3 further increased the value of ionic conductivity and decreased the activation energy of the GDC solid electrolyte compared to the addition of Fe2O3. The highest ionic conductivity and the lowest activation energy were obtained in the sample with 2.5% Nd2O3 in 650oC operating temperature, with the values achieved were 1.2 mS/cm and 0.41 eV, respectively. Therefore, it can be concluded that Nd2O3 addition is more effective to improve the performance of solid electrolyte GDC.